Brain Derived Neurotrophic Factor (BDNF) As a Predictive Biomarker of the Occurrence of Post Traumatic Stress Disorder (PTSD) - Belhadj-Tahar, H.; Sadeg, N. (Highlights on Medicine and Medical Science Vol. 1, 2021)
The primary goal of the pilot study was to determine the rate of serum BDNF and the initial clinical course of a subject who had been exposed to a potentially traumatic incident over the course of three months. In this study 12 volunteers were recruited, 7 have been exposed to a traumatic event and 5 negative controls without psycho-trauma history. In this study, there is no correlation between circulating levels of cortisol and BDNF. The following are the findings of this study: In comparison to the control group, the rate of BDNF was substantially lower in the trauma group of volunteers: 6.20±1.73 ng / ml for the group with trauma versus 21.79±1.76 ng / ml for the control group with p<0.001. When compared to those who have experienced a traumatic event, the rate of serum BDNF is substantially reduced in victims of physical aggression: 4.36±0.37 ng / ml Assault group versus 6.94±1.44 ng / ml control group event with p = 0.03. The level of BDNF is significantly inversely correlated with the intensity of the Peritraumatic distress (r = -0.75, p <0.05). When compared to the group without PTSD, the rate of serum BDNF was significantly lower in the group with acute PTSD: 7.5±0.9 ng / ml in the absence of PTSD (n = 4) versus 4.5 ±0.4 in the presence of PTSD (n = 3), p = 0.001.